ইসলামে বিনোদন ব্যবস্থা: একটি প্রাথমিক বিশ্লেষণ | Recreation in Islam: A Preliminary Analysis (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Islam is a balanced way of life which acknowledges the natural temperament of human being. All the injunctions and rulings of Islam are both simply easy and elegantly mannered. As it encompasses all aspects of human life, it has paid special importance to the sound growth of human beings both spiritually and physically. To that ends, it has provided proper guidelines regarding recreation which plays a crucial role with regard to the mental growth of human being. An introduction to recreation, attitudes of Islam towards recreation, its parameter, characteristics and principles of recreational activities allowed by Islam,  and various types and ways of recreation in the time of  Rasul (S.) and Sahaba Kiram (R.) have been presented in this article. The article has mainly been accomplished in descriptive and analytical manner. After reading this article, people would understand all the recreations which are approved by Islam. Besides this, they would be inspired to practice sound and superb recreational activities and encouraged to avoid all the shameless and nude steps that run in the society under the aegis of recreation.সারসংক্ষেপ: ইসলাম মানুষের স্বভাব-প্রকৃতির সাথে সামঞ্জস্যশীল পরিপূর্ণ একটি জীবনবিধান। এর বিধানাবলি যেমন সহজ-সাবলীল, তেমনি তা সুষ্ঠু রুচি সম্পন্নও বটে। এ ব্যবস্থা মানবজাতির দেহ ও মনের সুস্থ বিকাশ সাধনে সবিশেষ গুরুত্ব প্রদান করেছে। যারই প্রেক্ষিতে মানুষের জীবনের নানা গুরুত্বপূর্ণ বিষয়ের পাশাপাশি চিত্ত বিনোদনের ব্যাপারেও সঠিক ও যথার্থ নির্দেশনা পেশ করেছে। অত্র প্রবন্ধে বিনোদনের পরিচয়, এ ব্যাপারে ইসলামের দৃষ্টিভঙ্গি, ইসলাম প্রদত্ত বিনোদন ব্যবস্থার বৈশিষ্ট্য ও মূলনীতি, এর সীমারেখা এবং রাসূল স. ও সাহাবা কিরাম রা.-এর সময়কালে বিনোদনের বিভিন্ন ধরন-পদ্ধতি সংক্ষেপে উপস্থাপন করা হয়েছে। প্রবন্ধটি মূলত বর্ণনা ও বিশ্লেষণমূলক ধারায় সম্পন্ন করা হয়েছে। প্রবন্ধটি থেকে ইসলাম অনুমোদিত বিনোদনের বিবরণ জানার পাশাপাশি সুস্থ ও রুচিশীল বিনোদনমূলক কর্মকাণ্ড চর্চা এবং বিনোদনের নামে সমাজে প্রচলিত নানা অশ্লীল ও অনৈতিক কাজকর্ম পরিহার করার অনুপ্রেরণা পাওয়া যাবে ।